(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: This study was aimed at understanding adolescents conceptions regarding health. Methodology: This was an empirical study conducted applying qualitative methods in a village at Sylhet district in the northeastern region of Bangladesh. Data were collected through in-depth interviews and Focus Group Discussions (FGDs). Result: Most of the adolescents did not have clear conception about the meaning of the term Health in term of WHOs definition. They emphasized that the appearance of body structure is the indicator of health. They divided human body into two parts; inner and outer. The flesh and intestine are covered by skin. Soul is considered as the internal part of body. Respondents explained that female body as less strong than male and female become easily infected. Few adolescents believed health as state of disease free condition. Conclusion: This study revealed that adolescents have diversified thinking on health which demands to provide special attention for improving their understanding on health. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13350 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.30-33